2015
DOI: 10.1080/09500340.2015.1093662
|View full text |Cite
|
Sign up to set email alerts
|

Average BER performance of FSO SIM-QAM systems in the presence of atmospheric turbulence and pointing errors

Abstract: This paper presents the exact average bit error rate (BER) analysis of the free-space optical system employing subcarrier intensity modulation (SIM) with Gray-coded quadrature amplitude modulation (QAM). The intensity fluctuations of the received optical signal are caused by the path loss, atmospheric turbulence and pointing errors. The exact closed-form analytical expressions for the average BER are derived assuming the SIM-QAM with arbitrary constellation size in the presence of the Gamma-Gamma scintillation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 29 publications
0
10
0
1
Order By: Relevance
“…Here, either the Gamma-Gamma or the Gamma distribution is used. The former has been proven that models accurately enough weak-to-strong turbulence conditions, while the latter provides a less complicated model and additionally, it has been demonstrated that is accurate enough, mainly for weak turbulence conditions, [3,9,12,15,19,23,26,27,[30][31][32][33]. It should be mentioned here that the Gamma distribution has been studied and gives very accurate results, especially, for satellites' optical up/downlinks under weak turbulence conditions, [26,27,33].…”
Section: Set-up Of the System And Channel Modelmentioning
confidence: 92%
See 4 more Smart Citations
“…Here, either the Gamma-Gamma or the Gamma distribution is used. The former has been proven that models accurately enough weak-to-strong turbulence conditions, while the latter provides a less complicated model and additionally, it has been demonstrated that is accurate enough, mainly for weak turbulence conditions, [3,9,12,15,19,23,26,27,[30][31][32][33]. It should be mentioned here that the Gamma distribution has been studied and gives very accurate results, especially, for satellites' optical up/downlinks under weak turbulence conditions, [26,27,33].…”
Section: Set-up Of the System And Channel Modelmentioning
confidence: 92%
“…In order to investigate the scintillation's influence on the performance variations, many statistical models have been proposed. One of them is the Gamma-Gamma distribution which has been proved that is accurate enough for weak-to-strong turbulence conditions, [3,9,12,19,23,[30][31][32]. Another, accurate one, mainly for weak turbulence conditions, is the Gamma model which has the additive, important advantage that is given by a not very complicated mathematical expression compared with others distributions' expressions, [26,27,33].…”
Section: The Gamma-gamma and The Gamma Distribution Modelsmentioning
confidence: 97%
See 3 more Smart Citations